Investigation on the removal efficiency of inclusions in Al-killed liquid steel in different refining processes. (3rd July 2017) - Xu, J.; Huang, F.; Wang, X.; Jing, C.; Guo, X.
Abstract : Industry trials were carried out to study the removal efficiency of inclusions in Al-killed liquid steel in the processes of BOF–LF–RH–CC and BOF–RH–CC. It was found that the removal efficiency of inclusions has a high dependence on inclusion types. Solid inclusions are more easily to be removed than liquid inclusions. The removal efficiency of solid Al2 O3 inclusions is higher than that of solid CaO–Al2 O3 –MgO inclusions. As liquid CaO–Al2 O3 –MgO inclusions coexisted with solid CaO–Al2 O3 –MgO inclusions in the liquid steel, the low removal efficiency of inclusions in RH degassing process was found in BOF–LF–RH–CC process. However, high removal efficiency and ultra-low total oxygen (T.O) content were obtained in BOF–RH–CC process because the inclusions were mainly composed of solid Al2 O3 although initial T.O content before RH degassing was relatively high. This is due to the fact that solid Al2 O3 tends to form cluster-shaped inclusions which have both a higher contact angle and a lower work of adhesion with steel than calcium aluminate, resulting in easier removal by RH degassing. Therefore, it is proposed to weaken steel–slag reaction and calcium treatment before RH degassing to retain solid Al2 O3 inclusions in the steel.